Measurement of exclusive D meson decays to η and η′ final states and SU(3) amplitude analysis - Artuso, M; Blusk, S; Khalil, S; Li, J; Mountain, R; Nisar, S; Randrianarivony, K; Sultana, N; Skwarnicki, T; Stone, S; Wang, J; Zhang, L; et al. (2008)
Using 281pb-1 of data collected with the CLEO-c detector, we present new measurements of Cabibbo-suppressed decays of D0 and D+ mesons to η and η′ final states. We make first observations of D0→η′ π0, ηη, ηη′, and ηπ+π-, and find evidence for D+→ηπ+π0, D+→η′π+π0, and D0→η′π+π-. We also report on improved measurements of D0→ηπ0, D+→ηπ+, and D+→η′π+. Using the measured two-body Cabibbo-suppressed decays, we extract amplitudes for specific flavor topologies and compare them to those from Cabibbo-favored decays. © 2008 The American Physical Society.